Frontispiece: A Bistable Microelectromechanical System Actuated by Spin‐Crossover Molecules. Issue 28 (3rd July 2017) - Manrique‐Juarez, Maria D.; Mathieu, Fabrice; Shalabaeva, Victoria; Cacheux, Jean; Rat, Sylvain; Nicu, Liviu; Leïchlé, Thierry; Salmon, Lionel; Molnár, Gábor; Bousseksou, Azzedine
Abstract : Microelectromechanical Systems In their Communication onpage 8074 ff. G. Molnár, A. Bousseksou et al. describe a microelectromechanical element actuated by a spin‐crossover ferrous complex. Switching from low‐ to high‐spin state of the ferrous ions leads to reversible bending of a cantilever.